CODESRIA Bulletin Online, No. 27, December 2021 - Rethinking Social Policy in Africa: A Transformative Approach: Katja Hujo - Hujo, Katja (CODESRIA Bulletin, 2021)
Introduction More than a decade ago, former UNRISD director Thandika Mkandawire developed the concept of transformative social policy (TSP), the understanding that social policy, beyond its obvious protective function, also plays productive, reproductive and redistributive roles (Mkandawire 2004; UNRISD 2006). This approach, which soon guided the entire social policy research and policy work at UNRISD, was in many regards a game changer. It encouraged a focus on the real challenges that social policy faces in a development context, characterised by the need to foster structural transformation, dynamic accumulation processes and socio-political change. It triggered a multi-disciplinary inquiry to which economists could contribute alongside sociologists, gender experts, political scientists, legal scholars, historians and anthropologists. It connected the development literature with the social policy literature, helping to overcome Western bias in social policy scholarship, and the social policy blindness of development theory. And it helped to do away with the myth that social policy was largely an instrument for rich countries, but not suited for lower-income countries lacking the basic preconditions for issues such as formal wage employment, effective state bureaucracy or fiscal space. In this article, I will emphasise the transformative role of social policy and talk about the ‘social turn’ in development thinking and practice we have witnessed in the last two to three decades, and its limitations. I will then zoom in on the African context, and finally, I discuss what rethinking social policy in Africa could imply, and which lines of thinking could inspire a new approach to social policy in the region and beyond. The ‘social turn’ and its limitations We are all familiar with the arguments that reduced the remit of social policy to a residual role. In the 1970s and 1980s, neoclassical and monetarist economists became increasingly influential, associating social policies with fiscal crisis, inflation and negative impacts on efficiency. This contrasted starkly with the preceding Keynesian paradigm that saw a mutually beneficial relationship between economic development and universal social policies for achieving a stable accumulation process via active demand management and a smoothing of the business cycle. It meant that the state had to intervene by institutionalising policies that would guarantee the income of the unemployed and stabilise demand, and to respond to income loss across the life-cycle as the result of social contingencies (childhood, maternity, sickness, work accidents and disability, old age, etc.). While the Keynesian policy approach (which also had problems in terms of its practical application, in particular the neglect of monetary constraints such as inflation) was not fully applied in the developing world, given a variety of limitations to it, there was a developmental period in the post-war era that led to significant progress in economic and social development dimensions in different regions, and which for many still serves as a benchmark for what is possible. In contrast to the Keynesian model, interestingly the neoliberal approach was fully and radically applied in the developing world after the collapse of the previous model, to a much greater extent than in the Western hemisphere, where social-democratic and conservative continental European welfare regimes, to use the EspingAnderson classification (EspingAnderson 1990), demonstrated greater path dependency, resisting the dismantling of state-led development for a longer period. The policy recommendations and conditionalities of the neoliberal turn in development and social policy were expenditure cuts, privatisation of social protection systems and a general shift towards social funds, safety nets and marketbased schemes. Trade as well as financial and capital markets were liberalised and deregulated at a global scale, but the expected economic miracles did not materialise, the social costs of stabilisation and structural adjustment policies (SAPs) were huge, and the discussion about what role social policy had to play within the development process remained contested (Mkandawire and Soludo 1999; Adesina 2004; 2010). Two developments in over four decades of neoliberal practices had a major impact on the policy debate: the afore-mentioned disappointing results of the model in terms of social development, as well as the wave of economic and financial crises that started in the late 1980s, continued in the 1990s and culminated in the global economic and financial crisis in 2008 (Hujo 2005). According to Polanyi’s double movement theory, after the laissez-faire and free market euphoria came the counter-movement demanding protection against adverse market effects (Polanyi 1978 [1944]). UNRISD has labelled this latest comeback of social policy in the international development discourse the ‘social turn’, defined in its 2016 flagship report as a ‘combination of shifts in ideas and policies that has reasserted social issues in development agendas’ (UNRISD 2016: 34). The need to re-establish a comprehensive definition of social policy had been articulated in the late 1980s, but the social turn got its real drive internationally through the World Summit for Social Development of 1995, held in Copenhagen. The Copenhagen summit suggested a more integrated approach, which would link poverty reduction with social inclusion and employment creation as an alternative to the neoliberal model. Participants also rejected the trickle-down assumptions that link liberalisation to a virtuous circle of growth, employment generation and poverty reduction, as well as the notion that the key social function of governments should be restricted to the provision of safety nets. Since the turn of the millennium in particular, the need for a more proactive approach to eradicate poverty, reduce inequality and protect people against risks associated with market economies, and social contingencies across the life-cycle, has gained currency. Global social policy agendas that were designed in that period, such as the Millennium Development Goals, Education and Health for all initiatives, or the ILO Social Protection Floor Recommendation No. 202, are further examples of this growing recognition (UNRISD 2016). In practice, however, the social turn had severe shortcomings. Several of the key instruments and interventions promoted by the international donor community did very little against the drivers of social exclusion and economic stagnation (which was the result of designing policies based on a protective or welfarist approach, neglecting production and other functions of social policy). Far from being transformative, they have reproduced the problems they were meant to address. This was mainly the result of endorsing rather than questioning mainstream orthodox economic recipes such as austerity or privatisation and ignoring unequal power relations. Another prominent example of the shortcomings of the contemporary social turn is the uncritical promotion of conditional cash transfer (CCT) and public works programmes, which often narrowly target specific populations or provide minimal benefits for a limited time period without providing a long-term solution to chronic poverty and the absence of comprehensive social protection systems. Social policy in the African context Social policy varies according to the political and economic models that prevail in a specific country and during a specific historical period. And while there is a certain path dependency, or continuity, associated with welfare regimes, social policy also evolves in response to different external and internal challenges and risks, or opportunities (Hujo and Yi 2016). The global economic crisis that started in 2008 clearly highlighted the new global political and economic context in which these risks and challenges unfold: globalisation and financialisation; persistent poverty and rising inequality; technological progress coupled with a growing technological divide; postindustrial demographic change; and the rise of the service sector, characterised by the sharp contrast between sophisticated services relying on new technologies and highly skilled labour, and a growing number of poor service providers struggling for a livelihood in the informal economy. These changes are interlinked and have reinforcing and contradictory impacts on society – in the areas of global and national finance for development; employment, productivity and wages; vulnerability and poverty; inequality and the environment. Turning to social policy in Africa, these policies have to be understood, then, in terms of their specific history and country context, and according to whether they respond successfully or less successfully to the new challenges and risks I have outlined. Africa, like Latin America, has been a laboratory of development models and donor practices, especially after the global debt crisis of the early 1980s paved the way for a stronger integration of African economies into global markets. To define social policy models or welfare regimes in Africa is a difficult task, not only because the traditional approaches developed in the classical literatures are often not suitable and new classifications are not entirely satisfactory, but also because the continent’s more recent history has seen an increasing hybridisation of models and fragmentation of approaches, rather than a consolidation of a social model that could easily be linked to a dominant mode of production, such as a market, family or state economy. Social policy approaches in Africa were shaped by colonial history, when rudimentary social policy systems were introduced following the respective European models. These were aligned with the requirements of a specific pattern of incorporation in the colonial economy –for example, cash crop economies in West Africa versus labour-reserve economies in Southern Africa, as Mkandawire has shown in his seminal works about colonial heritage and welfare and tax regimes in Africa (Mkandawire 2010; 2020). What I find especially interesting in this work is that contestation and rupture were crucial to adapt these models to new state visions in the post-independence era, post-conflict situations or periods of political transition, for example after the end of apartheid regimes, rectifying old injustices and adapting schemes to current challenges. Secondly, social policy approaches in sub-Saharan Africa were influenced by factors such as economic crises, donor influence and generalised institutional crisis driven by SAPs, which had resulted in economic polarisation, fragmented social identities and a backlash against the post-independence modernisation project (Bangura 1994). This crisis in the public sector was then meant to be fixed through public management approaches and good governance reforms in the 1990s, but the neglect of social relations and an enabling environment for institutional reform led to widespread failure of this agenda; and the necessary resources and administrative capacities to expand what had started as a universal approach in many countries after independence could not be maintained (Bangura and Larbi 2006). The traditional social policy definition (see, for example, UNRISD 2010: Chapter 5) comprises social insurance schemes, social assistance programmes and labour market policies (in addition to the social services that were the primary focus of post-independence African states), which are either directly financed and provisioned through the state, or at least regulated by the state. However, this conception of social policy could not be successfully emulated in the African context for several reasons. Firstly, the coverage of formal contributory insurance remained low in contexts of high economic informality; secondly, it declined further when public sector workers were retrenched in large numbers during structural adjustment; and thirdly, in the case of public services such as education and health, which had started off ambitiously in many countries in the post-independence period, their subsequent privatisation and dismantling resulted in fragmented, unequal and underfunded systems, with negative impacts on access and quality. The results of these social policy responses to a changing global context and recurrent crises have been mixed. Poverty, while reduced in some countries, has not been eliminated, and inequality has actually increased in developed and developing countries. Poverty in absolute numbers has increased in sub-Saharan Africa, and in many countries in the region the majority of the population still lives in poverty and precariousness. In sum, the social systems that were meant to be built over several generations in tandem with economic development and in a synergistic way stalled, or more correctly, were aborted prematurely, with the state losing its steering and coordinating function in both social and economic policy. This loss of steering capacity meant reacting to and accommodating the exigencies of a globalised market economy, represented by donors, IFIs, Multinational Corporations and large investors, rather than negotiating with and responding to the claims of ordinary citizens and national interest groups to move forward a home-grown, long-term development vision. This loss of policy space and state capacity, but also the worsening of state–citizen relations, and the fact that democratic regimes often appeared to be ‘choiceless’ or ‘disempowered’ (Mkandawire 2006) in the face of external constraints and interferences, go indeed a long way to explain the bad governance, patronage, rent-seeking and corruption that have haunted the continent. Rethinking social policy in Africa: four ideas In the last part of this article I would like to sketch four ideas for rethinking social policy in Africa and beyond. Combining productivist with rights-based approaches to social policy We have already discussed the need for a productivist approach to social policy, but certain aspects of this approach have also been criticised, especially the linking of entitlements with formal employment, as this excludes all those in the informal economy or engaged in unpaid care and domestic work. Advocating for delinking social rights from employment became popular, as the expansion of tax-financed social assistance schemes and debates on basic income demonstrate. There are, however, many good reasons to maintain the link between labour and capital through social insurance – for example, to keep employers responsible for financing social insurance schemes and social services, and to emphasise the productive contribution of informal workers, which can enhance their bargaining position in claiming support from business and the state (Alfers, Lund and Moussié 2017). Indeed, an either/or approach between a productivist and a rightsbased approach to social policy is counterproductive, as both need to be pursued simultaneously (Alfers, Lund and Moussié 2017; Heintz and Lund 2012; UNRISD 2013). Integrating questions of sustainable financing into social policy Today, in a context of mounting uncertainty with regard to aid flows, and with many rich economies in crisis, the mobilisation of domestic resources is increasingly important for achieving development goals. This is highlighted in the Addis Ababa Action Agenda for Finance for Development as a key means of implementing the Sustainable Development Goals (UN 2015a; 2015b; UNRISD 2016). While more attention to financing challenges is laudable, what is often neglected are the productive, redistributive, reproductive and protective implications of different financing instruments (UNRISD 2010), the consequences of power imbalances between actors engaged in fiscal and revenue bargains, the political factors that impact on the potential to mobilise resources, as well as constraints emerging from the international context (Hujo 2020). Broader questions, such as rising inequality and environmental problems One of the greatest challenges of our time is the rise in inequality, within and between countries, and vertical and horizontal inequalities related to income and group differences. Economic models determine to a great extent who benefits from growth processes, and to what extent redistribution happens through tax and social policies, or other regulations for investors and wealth owners. Social policy needs to integrate affirmative action and interventions targeted at specific groups into a universal framework that benefits and is supported by all people, in order to maintain the necessary linkages between classes, generations, genders or national groups, etc., to promote a sense of national identity and social cohesion. Climate change and environmental sustainability are equally at the top of the international agenda since states launched the 2030 Agenda for Sustainable Development in 2015. Sustainability is not a new subject, but historical memory is again short. The 1970s and 1980s featured emancipatory ecological movements from below in a variety of countries, which included a different vision of the economy and society, before the topic was captured by corporate and political elites who brought in a business mindset and the commodification of nature as the solution. What does the environmental challenge mean for TSP? In UNRISD, eco-social policies have been analysed as an integrated approach to this challenge, but social policies that have a clear environmental dimension are still rare, and often fall into the public works or CCT category –for example, the Indian MNREGA employment scheme or the Brazilian Bolsa Verde programme. We need more debate and analysis on how to harness social policies for environmental sustainability, for example with regard to social services and infrastructure, labour market policies and social security. Consider the politics of social policy making: who drives transformative change? Next to structural factors, agency is a key determinant of social policy. The power of ideas, the lasting impact of a generation of African leaders who did not shy away from substantive thinking and long-term visions, and the importance of non-state actors, civil society, voters, interest groups, social partners etc. in influencing and monitoring policy processes, discourses, social innovations and behaviour of corporations should be scrutinized in any serious attempt to understand social policy in a development context. After all, social policy is about politics and a social contract that is mutually beneficial, defining obligations and rights, creating the bonds, mutual support and trust that tie societies together, beautifully expressed in the Ubuntu philosophy as I am because we are.